Docking-Based Evaluation of LC–HRMS Metabolites from Fermented Mustard Greens on DNA Gyrase B and Xanthine Oxidase - Nasri; Cintya, Henni; Silalahi, Jansen; Haro, Ginda; Suci, Nurul; Kaban, Vera Estefania (Indonesian Journal of Applied Research (IJAR), 2026)
Fermented mustard greens (Brassica juncea L. Czern.) contain bioactive metabolites formed through lactic acid bacteria–driven biotransformation, yet their molecular targets related to antibacterial and antioxidant functions remain poorly understood. This study aimed to characterize key metabolites in fermented mustard greens and evaluated their potential inhibitory activity against DNA gyrase B and Xanthine Oxidase through an integrated LC–HRMS metabolomics and molecular docking approach. Untargeted LC–HRMS profiling identified 292 metabolite features, from which five compounds—gentisic acid, trans-cinnamic acid, xanthurenic acid, indole-3-lactic acid, and indole-3-acrylic acid—were structurally confirmed via MS/MS fragmentation. These metabolites were docked against DNA gyrase B (5D7R) and Xanthine Oxidase (3NVW) to predict binding affinity and interaction mechanisms. Xanthurenic acid exhibited the strongest interaction with DNA gyrase B (–7.6 kcal/mol), forming hydrogen bonds with key catalytic residues, such as Asp81 and Ile86, which suggested ATP-competitive inhibition. Meanwhile, gentisic acid and indole-3-acrylic acid exhibited the most favorable binding to Xanthine Oxidase (–7.2 kcal/mol), characterized by π–π stacking with Phe914 and Phe1009 and hydrogen bonding to Glu802, indicating dual antioxidant and anti-hyperuricemic potential. These findings highlighted fermented mustard greens as a promising functional food source containing metabolites with predicted antibacterial and XO-inhibitory activities. Further in vitro and in vivo validation is required to confirm these computational insights.